Prescription, dispensation and marketing patterns of methylphenidate - Perini, Edson; Junqueira, Daniela Rezende Garcia; Lana, Lorena Gomes Cunha; Luz, Tatiana Chama Borges (Revista de Saúde Pública, 2014)
OBJECTIVE To analyze the patterns and legal requirements of methylphenidate consumption. METHODS We conducted a cross-sectional study of the data from prescription notification forms and balance lists of drugs sales – psychoactive and others – subject to special control in the fifth largest city of Brazil, in 2006. We determined the defined and prescribed daily doses, the average prescription and dispensation periods, and the regional sales distribution in the municipality. In addition, we estimated the costs of drug acquisition and analyzed the individual drug consumption profile using the Lorenz curve. RESULTS The balance lists data covered all notified sales of the drug while data from prescription notification forms covered 50.6% of the pharmacies that sold it, including those with the highest sales volumes. Total methylphenidate consumption was 0.37 DDD/1,000 inhabitants/day. Sales were concentrated in more developed areas, and regular-release tablets were the most commonly prescribed pharmaceutical formulation. In some regions of the city, approximately 20.0% of the prescriptions and dispensation exceeded 30 mg/day and 30 days of treatment. CONCLUSIONS Methylphenidate was widely consumed in the municipality and mainly in the most developed areas. Of note, the consumption of formulations with the higher abuse risk was the most predominant. Both its prescription and dispensation contrasted with current pharmacotherapeutic recommendations and legal requirements. Therefore, the commercialization of methylphenidate should be monitored more closely, and its use in the treatment of behavioral changes of psychological disorders needs to be discussed in detail, in line with the concepts of the quality use of medicines.